Do computer simulations for teaching the balance scorecard improve learning? An experiment with management accounting students - Lopes, A.I.; Capelo, C.; Mata, A. ("XXIV Jornadas Luso-Espanholas de Gestão Científica: Contributo da Gestãopara a Sustentabilidade das Organizações e da Sociedade", 2014)
This article addresses the effectiveness of teaching the Balanced Scorecard (BSC) using a business simulator for testing a set of hypotheses about the influence of simulation on the students’ understanding of this management system. This experience with undergraduate students was specifically designed to promote learning the BSC. Up to now a growing number of organizations around the world are using the BSC to define, implement and manage strategy. Nonetheless, some studies points out problems and limitations associated with its implementation and use, part because it seems that managers do not understand the fairly independence of measures and perspectives and do not always mirror the recommended cause-and-effect logic included in the systems perspective of the BSC approach. Our findings, based on student feedback and assessment, showed that the simulation significantly enhanced the understanding of the BSC concepts related to the strategic management and double-loop learning processes and the systems perspective.